Green biorefinery of walnut husk: Phenolic extraction and ethanol production - Elham Momen; Behzad Satari (Applied Food Research)
Microwave and ultrasound techniques were utilized on walnut green husk (WGH) to extract valuable phenolic compounds and enhance the residual biomass's susceptibility to hydrolysis for subsequent ethanol production. The aim was to optimize process variables in order to achieve an integrated biorefinery with the zero-waste-base standpoint. For microwave-assisted extraction (MAE), four-time levels (0.5, 1.0, 2.0, and 5 min) and power settings (300, 450, 600, and 800 W) were tested. Ultrasound-assisted extraction (UAE) was conducted at a frequency of 28 kHz and power of 100 W over varying time intervals (2, 6, 10, 14, 18, and 22 min). Generally, higher power settings and longer extraction times produced higher contents. Specifically, the maximum total phenolic content (TPC) (220.13 mg GAE/g-DW), total flavonoid content (TFC) (63.21 mg catechin/g-DW), and DPPH scavenging activity (86.13 %) were achieved using the highest power and longest extraction time for MAE. Similarly, the longest UAE time resulted in the highest TPC (214.32 mg GAE/g-DW), highest TFC (58.44 mg catechin/g-DW), and DPPH scavenging activity (76.15 %). Moreover, increased microwave power and longer extraction times favored glucose and ethanol yields, with maximum yields of 55.30 % and 36.67 %, respectively, obtained at 800 W for 5 min. For UAE, the highest glucose and ethanol yields (52.33 % and 34.16 %, respectively) were obtained at 22 min. Conversely, lower extraction times and power settings for microwave, as well as shorter ultrasound times, were beneficial for lignin removal. The application of MAE and UAE in the WGH biorefinery process enhanced the extraction of phenolics and improved biomass hydrolysis, leading to more efficient, sustainable, and economically viable production of biofuels and bioproducts.